Development of cost effective integrated automatic head light dipping system and obstacle detection for safe night driving system - Thirumala Akash K, Yuvateja Chilukuri, Raji C, Shailaja T, Y Hema Prakash (International Journal of Advanced Science and Technology, 2020)
The purpose of the paper is to minimize the problem of road accidents during night and also ensure the safer night rides in the vehicles, by using this automated system in vehicles. The high beam coming from the light source of vehicle will be uncomfortable for a driver, and causes temporary blindness when a high beam intensity of light falls on human eye. The objective of this work is to reduce such effect of glare, and damage caused by it on retina of eye. The proposed model can almost reduce the threat of accidents by dipping the headlights of the vehicle between high and low beams automatically whenever there are vehicles passing by, and also warn the driver about the protruding obstacles on the road as well as display the distance of the obstacles from the vehicle on a display. As safety is the major concern these days, if all the vehicles could assemble this automated system, it will reduce strain to the driver in dipping the lights during heavy traffic and reduce the risk of tragic accidents that could happen because of an after image effect caused in human eye due to exposure of high intensity light. The available systems in the market are expensive hence our project aims at designing a simple and cost effective automated head light dipping system integrated with obstacle detection. This system ensures to dip the light automatically between high and low beams as many times as possible, whenever there is an approaching vehicle during night and also detects the obstacles and displays their distance form our vehicle. This work has a scale of 75% cost effectiveness compared to the existing market prices.